Characterization of a Novel 2018 Influenza Virus Outbreak on the Yucatan Peninsula, Mexico, in the Summer - Lumumba Arriaga-Nieto; David Alejandro Cabrera-Gaytán; Alfonso Vallejos-Parás; Porfirio Felipe Hernández-Bautista; Clara Esperanza Santacruz-Tinoco; Julio Elías Alvarado-Yaah; Yu-Mei Anguiano-Hernández; Bernardo Martínez-Miguel; María Erandhí Prieto-Torres; Concepción Grajales-Muñiz; Nancy Sandoval-Gutiérrez; Horacia Celina Velarde-Scull (Microorganisms)
During the 2017–2018 influenza season, there was high influenza activity, with a predominance of influenza A(H1N1)pdm09 circulation in the country. The influenza circulation pattern in the area of the Yucatan Peninsula was different from that of the rest of the country. However, in the summer of 2018, there was a sudden increase in the number of identified cases. A retrospective analysis was performed using data generated by four molecular diagnostic laboratories of the Mexican Social Security Institute. Demographics, influenza positivity, seasonality and case fatality rates were recorded. We used odds ratios to compare outpatients who were confirmed by laboratory tests to be positive with those who were confirmed to be negative. The Kaplan–Meier method and Cox multivariate analysis were used to calculate cumulative risk. There were 4460 cases of ILI/SARI between Yucatan and Quintana Roo, which represented 53.1% of the total number of cases reported. Compared with that in 2009, the epidemic wave in 2018 was shorter and more expansive, with a greater number of reported cases, as well as a greater number of people who required hospitalization. The dominant pattern of A(H1N1)pdm09 influenza activity on the Yucatan Peninsula in the summer of 2018 has not been observed since the influenza pandemic of 2009.